"Minor" literature of an itinerant culture: Goulet, Campbell, and the Canadian Métis. Issue 2 (July 2020) - Rehill, Annie
Abstract : The Canadian Métis population historically was marginalized and then oppressed, yet retains cultural vibrancy. The movement and adaptation necessary to survive became defining characteristics of their artistic expression, and the Métis who once spoke French and autochthonous languages now speak mostly English, albeit embroidered with traces of previous languages. Examining Métis literature reveals how language migrates, adapts, and transforms as a living phenomenon, in a Deleuzo-Guattarien process of continual movement, plateau-reaching, and regrouping while seeking new favorable environments (which means the ability to work, which increasingly means speaking English in this context). This historical literary unfolding is traced here in works by Louis Goulet, Maria Campbell, Marilyn Dumont, and Rita Bouvier, to demonstrate the development of a minor literature as defined by Deleuze and Guattari, and of a literature that emanates from a culture of inclusivity and itinérance as described by François Paré, who focuses on the French-Canadian diaspora beyond Quebec. Métis literature is resistant by nature, representative of a population that is not in the majority. The writings considered here share fundamental characteristics of numerous other minority literary expressions of survival and resistance. In addition to Deleuze and Guattari and Paré, helpful critical perspectives include those of Pamela Sing, Emma LaRocque, and Gloria Anzaldúa.